Improving research about us, with us: a draft framework for inclusive autism research. Issue 5 (28th May 2017) - Chown, Nick; Robinson, Jackie; Beardon, Luke; Downing, Jillian; Hughes, Liz; Leatherland, Julia; Fox, Katrina; Hickman, Laura; MacGregor, Duncan
Abstract: It is both epistemologically as well as ethically problematic if the autistic voice is not heard in relation to social scientific research seeking to further develop knowledge of autism. Ever since autism first emerged, it has remained medicalised and almost exclusively the preserve of non-autistic researchers. More recently, autistic individuals have begun to contribute to autism research. However, the vast majority of research in autism is still undertaken on autistic people, rather than with them, and is often not concerned with improving the day-to-day lives of people with autism. We discuss the concepts of participatory research and emancipatory research before presenting a draft framework for what we regard as truly inclusive research in autism. Our proposals are firmly based on ideas developed by the members of a university-based group of autistic adults (the Asperger's Consultation Group) as well as the knowledge and experience of the other contributors.